2006
DOI: 10.1002/sce.20176
|View full text |Cite
|
Sign up to set email alerts
|

Predators of knowledge construction: Interpreting students' metacognition in an amusement park physics program

Abstract: ABSTRACT:It is recognized widely that learning is a dynamic and idiosyncratic process of construction and reconstruction of concepts in response to new experiences. It is influenced by the learner's prior knowledge, motivation, and sociocultural context. This study investigated how year 11 and 12 physics students' metacognition influences the development of their conceptual understandings of kinematics. An interpretive case study approach was used to investigate students working in collaborative groups in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 27 publications
2
50
0
12
Order By: Relevance
“…Metacognition has commonly been viewed as an individual's knowledge, control, and awareness of his/her thinking and learning processes (Baird & White, 1996;Gunstone, 1994;Kuhn, Amsel, & O'Loughlin, 1988). However, recent work has consolidated a broadened perspective of metacognition based on Flavell's (1976Flavell's ( , 1979 previous work that includes reference to students' knowledge and awareness of others' thinking and learning processes (Anderson & Nashon, 2007;Thomas, 1999;Thomas & McRobbie, 2001). This expanded perspective is consistent with sociocultural views of cognition that draw attention to the notion that students can and do learn to reason by reflecting on the processes by which others within their communities reason and by modifying accordingly their own thinking in ways they feel will benefit them.…”
Section: Introductionmentioning
confidence: 92%
“…Metacognition has commonly been viewed as an individual's knowledge, control, and awareness of his/her thinking and learning processes (Baird & White, 1996;Gunstone, 1994;Kuhn, Amsel, & O'Loughlin, 1988). However, recent work has consolidated a broadened perspective of metacognition based on Flavell's (1976Flavell's ( , 1979 previous work that includes reference to students' knowledge and awareness of others' thinking and learning processes (Anderson & Nashon, 2007;Thomas, 1999;Thomas & McRobbie, 2001). This expanded perspective is consistent with sociocultural views of cognition that draw attention to the notion that students can and do learn to reason by reflecting on the processes by which others within their communities reason and by modifying accordingly their own thinking in ways they feel will benefit them.…”
Section: Introductionmentioning
confidence: 92%
“…Metacognitive awareness involves the individual's awareness of the way in which he/she learns, constructs knowledge or develops understanding, as well as his/her knowledge of learning strategies, the demands of the learning task and his/her progress (Anderson & Nashon, 2007;Wilson & Johnson, 2000). Metacognitive awareness enables the learner to learn how, when and where to use cognitive strategies.…”
Section: Metacognitive Awareness and The Explicit Development Of Metamentioning
confidence: 99%
“…It follows then, that metacognition, which involves the thinking skills of awareness, active monitoring and executive control over one's learning (Brown, 1987;Flavell, 1976;White, 1988), is an important tool for meaningful learning. A review of the literature attests that students' active engagement of metacognition is key to developing deeper conceptual understanding (Anderson & Nashon, 2007;Baird & White, 1996;Flavell, 1987;Gunstone, 1994;Mintzes & Wandersee, 1998;Nashon & Anderson, 2004;White, 1993White, , 1998). An important goal for teachers, then, is to create a learning environment that enables students to become more self-aware of their own learning processes, including the ability to identify these processes and subsequently master (control) them in the service of learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Hisasaka et al studied metacognition with Grade 8 students in Japan and concluded that there are strong correlations between several dimensions of metacognition, in particular, behavioral evidencing of metacognition, evaluation and planning. Anderson and Nashon's (2007) study of high school students' metacognition while visiting an amusement park demonstrated that the key dimensions of awareness, monitoring and evaluation are critical to the resilience and sustainability of individual capacity to engage in meaningful learning. These dimensions can be developed, with the result that students are empowered in their learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation